The Feminist Killjoy Untangles Philanthropy<subtitle>Norway’s National Museum (Nasjonalmuseet) and Fredriksen Family Art Company Limited</subtitle> - Charis Gullickson (Kunst og Kultur)
In June 2019, The National Museum (Nasjonalmuseet) in Norway announced plans for a decade-long collaboration with Fredriksen Family Art Company Limited. The agreement gives the museum access to the Fredriksen collection of art and intends to generate a series of major exhibitions and significantly strengthen research. While this public-private partnership received some criticism in the press at the time, to date there is little or no academic research on the challenges of such an alliance. This article considers Sara Ahmed’s concept of the “feminist killjoy” as a method to untangle the complexity of philanthropy.